Local Delivery of a Novel Combination Immunotherapy Increases T Cell Infiltration and Significantly Improves Survival in a Poorly Immunogenic Model of Glioblastoma. (16th November 2020) - Haddad, Alexander F; Spatz, Jordan; Collins, Sara; Pereira, Matheus P; Gill, Sabraj; Montoya, Megan; Chuntova, Pavlina; Young, Jacob S; Mummaneni, Nikhil; Kasahara, Noriyuki; Aghi, Manish K
Abstract: INTRODUCTION: Glioblastoma (GBM) leads to severe systemic and local immune suppression, contributing to the failure of single-agent immunotherapies in clinical trials. Using gene therapy to deliver local combination immunotherapy consisting of cytokines and synthetic immunomodulators has been successful in other cancers. Each immunomodulator activates a specific part of the immune system, orchestrating a sustained response against cancer cells. A similar approach may be successful in GBM. METHODS: Immunomodulators included: IL-15 and IL-7 (T cell activation), LIGHT (T cell tumor infiltration), FLT3L (dendritic cell maturation/proliferation), a surface T cell engager (T cell killing of tumor cells), and a PD-L1 Bispecific T cell engager (T cell killing of cells expressing PD-L1). In vitro T cell killing assays were performed to assess T cell killing of SB28 mouse GBM cells expressing the combinatorial immunotherapy. Syngeneic C57BL/6 mice were then intra-cranially seeded with SB28 cells expressing the immunomodulators. The final experiment delivered immunomodulators to established SB28 intra-cranial tumors using neural stem cells (NSCs) and a replicating retrovirus (RRV) system. RESULTS: Naïve T cells kill SB28 tumor cells expressing the immunomodulators in vitro in a dose-dependent manner. Intracranial injection of SB28 tumor cells expressing the immunomodulators led to a significant survival benefit in experimental mice with a minimum survival of 60 days and three mice displaying long-term survival, as compared to a median survival of 20 days for control mice ( P  < .001). Significantly increased CD4+ and CD8+ T cell tumor infiltration was seen in treated mice on flow cytometry. Delivery of immunomodulators to established SB28 tumors using NSCs and an RRV system also resulted in a significant survival benefit in treated mice (median survival: 31 days vs. 22 days, P  < .001). Flow cytometry highlighted significant increases in CD4+ and CD8+ T cell tumor infiltration and a decrease in CD11b+ cell infiltration in treated mice. CONCLUSION: Our novel combination immunotherapy results in SB28 GBM tumor cell killing in vitro and in vivo, leading to a significant survival benefit and anti-tumor alterations to the GBM tumor microenvironment. Studies optimizing the delivery of the system are currently underway.